IBU RUMAH TANGGA DALAM MANAJEMEN KEUANGAN KELUARGA - Budi Gautama siregar (IAIN Padangsidimpuan, 2020)
Family is the smallest, most important and very basic in society and state. One problem in the family that can lead to divorce is a financial problem that cannot be managed properly. This paper is based on theoretical studies and previous studies. Financial management in the family is a way of managing family finances systematically and carefully through the planning, implementation and evaluation stages. Housewives in managing family finances must be smart, careful and precise in their use of finance so that a good family is always created and experiences continuous growth. With the ability of housewives to manage family finances appropriately, on time, right place, right price, and right quality will be realized family welfare.